Considerations on prognosis in psychiatry - Endara, Julio (1955)
Like the traveler, having traveled a long period of your itinerary, and perhaps fatigued by the incidents of the journey, a moment to contemplate the already distant prospect stops, the psychiatrist who has worked for the last thirty years, also experienced the need to take a break in your journey.